Electrical resistivity and wave character of free electrons in amorphous and nanoglass Sc75Fe25. (13th December 2017) - Ghafari, M; Hutchison, W D; Campbell, S J; Gleiter, H; Hahn, H; Feng, T
Abstract: The residual electrical resistivity of metallic amorphous alloys, ρ 0, is typically in the range 50 µ Ω cm < ρ 0 < 310 µ Ω cm corresponding to a mean free path of conduction electrons of order a few interatomic distances. In crystalline metals with low defect levels such as Cu however, the residual electrical resistivity is about ρ 0 ≈ 1.54 × 10 −2 µ Ω cm, leading to extensive progression of free electrons through the crystalline material, of typically up to 4 × 10 6 nm. The relatively 'high' values for the electrical resistivity of distorted Sc75 Fe25 alloys are discussed here within the framework of the wave character of electrons. The present investigation of amorphous and nanoglass Sc75 Fe25 over the temperature range 1.9–320 K, focuses on clarification of the temperature dependence of the resistivity, ρ ( T ). These alloys systems, which show a range of behaviours for temperature dependent resistivity—including temperature independent residual resistivity, as well as positive and negative polarities for the slope d ρ ( T )/d T —are examined in detail.